Does skill retention benefit from retentivity and symbolic rehearsal? - two studies with a simulated process control task - Kluge, Annette; Frank, Barbara; Maafi, Sanaz; Kuzmanovska, Aleksandra (Ergonomics, 2016)
Two experiments were designed to compare two symbolic rehearsal refresher interventions (imaginary practice, a hidden introspective process) and investigate the role of retentivity in skill retention. Retentivity is investigated as the ability to memorise and reproduce information and associations that were learned a short time ago. Both experiments comprised initial training (week 1), a symbolic rehearsal for the experimental group (week 2) and a retention assessment (week 3). In the first study, the experimental group received a symbolic rehearsal, while the control group received no rehearsal. In the second study, the experimental group received the same symbolic rehearsal used in study 1, enhanced with rehearsal tasks addressing human-computer interaction. The results showed that both symbolic rehearsal interventions were equally likely to mitigate skill decay. The retentivity showed medium to high correlations with skill retention in both studies, and the results suggest that subjects high in retentivity benefit more from a symbolic rehearsal refresher intervention. Practitioner Summary: Skill decay becomes a problem in situations in which jobs require the correct mastery of non-routine situations. Two experimental studies with simulated process control tasks showed that symbolic rehearsal and retentivity can significantly mitigate skill decay and that subjects higher in retentivity benefit more from refresher interventions.